2004
DOI: 10.1124/jpet.104.072553
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of the Osmosensitive Release of Taurine and d-Aspartate from SH-SY5Y Neuroblastoma Cells after Activation of M3Muscarinic Cholinergic Receptors

Abstract: The ability of muscarinic cholinergic receptors (mAChRs) to regulate the volume-sensitive efflux of two organic osmolytes, namely, taurine and D-aspartate, from human SH-SY5Y neuroblastoma cells has been examined. Incubation of the cells with hypoosmolar buffers resulted in an efflux of both osmolytes, with the threshold for release occurring at approximately 225 mOsM for taurine and D-aspartate. Inclusion of oxotremorine-M (Oxo-M), a muscarinic agonist, resulted in a marked enhancement of the volume-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
54
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(59 citation statements)
references
References 27 publications
5
54
0
Order By: Relevance
“…Moreover, the increase in receptor-mediated efflux of taurine from cholesterol-depleted cells was greater than that due to the increase in basal release alone, i.e., a synergistic, rather than additive, enhancement of receptor-mediated osmolyte efflux was observed for all three receptors (p Ͻ 0.01; paired Student's t test). Because previous studies of SH-SY5Y cells have extensively characterized the coupling of PAR-1 and mAChRs to volume-dependent taurine efflux (Heacock et al, 2004(Heacock et al, , 2006Cheema et al, 2007), in the current study, emphasis has been placed on monitoring the effects of cholesterol depletion and repletion on the activity of these receptor subtypes. In addition, the effects (if any) of CD on signal transduction events can readily be assessed by monitoring mAChRstimulated phosphoinositide turnover in these cells.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, the increase in receptor-mediated efflux of taurine from cholesterol-depleted cells was greater than that due to the increase in basal release alone, i.e., a synergistic, rather than additive, enhancement of receptor-mediated osmolyte efflux was observed for all three receptors (p Ͻ 0.01; paired Student's t test). Because previous studies of SH-SY5Y cells have extensively characterized the coupling of PAR-1 and mAChRs to volume-dependent taurine efflux (Heacock et al, 2004(Heacock et al, , 2006Cheema et al, 2007), in the current study, emphasis has been placed on monitoring the effects of cholesterol depletion and repletion on the activity of these receptor subtypes. In addition, the effects (if any) of CD on signal transduction events can readily be assessed by monitoring mAChRstimulated phosphoinositide turnover in these cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have demonstrated that receptor-mediated enhancement of osmolyte release is dependent on the degree of hypo-osmotic stress in SH-SY5Y cells (Heacock et al, 2004(Heacock et al, , 2006Cheema et al, 2007). Thus, the ability of cholesterol depletion to potentiate taurine release at different osmolarities was examined.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations